Measuring the effectiveness of cataract surgery: the reliability and validity of a visual function outcomes instrument. Issue 1 (1st January 1999) - Lawrence, D J; Brogan, C; Benjamin, L; Pickard, D; Stewart-Brown, S
Abstract : AIMS: To assess test-retest reliability and validity of the "TyPE" patient self assessed visual function questionnaire, as part of a study in two hospitals measuring the effectiveness of cataract surgery. The American TyPE questionnaire had minor adaptations made for use in Britain. METHODS: Test-retest reliability was assessed on 63 out of 378 adult cataract surgery patients in the study, using Spearman correlation coefficients and kappa coefficients of agreement. "Construct" validity was evaluated by comparing the association between changes in visual function questionnaire scores after surgery, with patients' perception of change in visual function obtained by independent interview of 24 patients. RESULTS: The TyPE questionnaire items showed very good test-retest reliability. Average Spearman and kappa coefficients for 39 patients from hospital 1 were 0.93 and 0.84 respectively. Spearman and kappa coefficients of 0.9 and 0.81 were obtained for those nine patients in hospital 2 where both the test and retest questionnaires were filled in by the same people. However, for the 15 patients from hospital 2, where the questionnaire was filled in by different people in the retest, reliability was less good: the Spearman coefficients were still high, average 0.72, but the kappa coefficients were poor, 0.27. Good construct validity was exhibited, with a correlation of 0.79 between change in distance vision score from the questionnaires and the independent interview. CONCLUSIONS: The adapted TyPE questionnaire is both very reliable and has good construct validity. The kappa coefficient should be used wherever possible to evaluate reliability. The test-retest reliability and validity and practicability of other visual function questionnaires have not been assessed adequately, and further development should be carried out of all such questionnaires, so that they may be introduced into routine clinical care.